EFEKTIVITAS METODE MULTISENSORI DALAM MENINGKATKAN KEMAMPUAN MEMBACA PADA PESERTA DIDIK DISLEKSIA DI SEKOLAH DASAR - ahilda Dea Komalasari (Elementary School: Jurnal Pendidikan dan Pembelajaran ke-SD-an, 2017)
This study aims to measure the effectiveness of multisensory method in improving the reading skills of dyslexia students in grades 2 SDN Tamasari 3Yogyakarta. This type of research is descriptive study that presents the change in theability of subject to read after receiving treatment. Subjects in this study were fivedyslexic students in second grade SDN Tamansari 3 Yogyakarta. Treatment usingmultisensory method given in the classical for four times with a duration of 2 x hours oflessons at each meeting. Early reading ability of subject is measured by asking thesubject to read simple words. Data collection technique used observation and tests. Thereading test results are analyzed using quantitative descriptive and observations wereanalyzed using qualitative descriptive. The description of the data showed an increase inreading skills dyslexic students. This was demonstrated by an increase in the number ofword recognition, reading time, and the number of words read per minute.Keywords: multisensory method, the reading ability of dyslexic students in elementaryschool.